Cutting Finite Element Simulation of Quenched Steel GCr15 Based on ABAQUS - Yang, Lin; Gong, Junhao; Liu, Jialiang; Xia, Jianqiu; Zhang, Yu (Recent Patents on Mechanical Engineering, 2024)
Background: The substantial cutting force and elevated cutting temperature during the machining of hardened steel GCr15 exacerbate tool wear. Objective: In this study, the influence of cutting parameters on cutting force and cutting temperature in the process of hard-cutting GCr15 was studied, the cutting parameters were optimized, and the cutting force and cutting temperature were predicted. Methods: The cutting simulation model was constructed using ABAQUS software, and the cutting force and cutting temperature were investigated under various cutting parameters through range analysis, variance analysis, and signal-to-noise ratio transformation analysis. Results: The simulation and experimental results demonstrated that the cutting force could be optimized by utilizing cutting speed vc=140 m/min, feed rate f=0.1 mm/r, and cutting depth ap=0.1 mm. Under these conditions, the cutting force in the x-direction was measured as 78.560N, while the cutting force in the y-direction was 32.423N. Moreover, for achieving the optimal cutting temperature, the recommended cutting parameters were cutting speed vc=120 m/min, feed rate f=0.1 mm/r, and cutting depth ap=0.4 mm. Conclusion: Compared to the conventional analytical method, which is burdened with high costs and low efficiency, the patent leverages finite element simulation technology to replicate the hardcutting process and its underlying cutting mechanism. This innovation simplifies the otherwise complex and laborious experimental and measurement procedures. By studying cutting force and cutting temperature, the optimization of cutting parameters can be achieved, thus offering valuable theoretical insights for practical production.
Keywords: GCr15